A deep view of a fossil relic in the Galactic bulge: the Globular Cluster HP 1. Issue 4 (5th January 2019) - Kerber, L O; Libralato, M; Souza, S O; Oliveira, R A P; Ortolani, S; Pérez-Villegas, A; Barbuy, B; Dias, B; Bica, E; Nardiello, D
ABSTRACT: HP 1 is an α-enhanced and moderately metal-poor bulge globular cluster with a blue horizontal branch. These combined characteristics make it a probable relic of the early star formation in the innermost Galactic regions. Here, we present a detailed analysis of a deep near-infrared (NIR) photometry of HP 1 obtained with the NIR GSAOI + GeMS camera at the Gemini-South telescope. J and K S images were collected with an exquisite spatial resolution (FWHM ∼0.1 arcsec), reaching stars at two magnitudes below the MSTO. We combine our GSAOI data with archival F606W-filter HST ACS/WFC images to compute relative proper motions and select bona fide cluster members. Results from statistical isochrone fits in the NIR and optical-NIR colour–magnitude diagrams indicate an age of $12.8^{+0.9}_{-0.8}$ Gyr, confirming that HP 1 is one of the oldest clusters in the Milky Way. The same fits also provide apparent distance moduli in the K S and V filters in very good agreement with the ones from 11 RR Lyrae stars. By subtracting the extinction in each filter, we recover a heliocentric distance of $6.59^{+0.17}_{-0.15}$ kpc. Furthermore, we refine the orbit of HP 1 using this accurate distance and update and accurate radial velocities (from high-resolution spectroscopy) and absolute proper motions (from Gaia DR2), reaching mean perigalactic and apogalactic distances of ∼0.12 and ∼3 kpc, respectively.